Penguatan Peran SDM pada Pasien Hipertensi Dengan Terapi Komplementer Berbasis Jus Pepaya - Formaida Tambunan; Erwin Silitonga; Edriyani Yonlafado Simanjuntak; Gloria Betania Samosir (Jurnal Pemberdayaan Masyarakat, 2025)
Hypertension is often referred to as a silent killer because most patients are unaware of their condition until serious complications occur, such as coronary heart disease, stroke, and chronic kidney failure. In the service area of Medan Deli Public Health Center, a curative mindset remains prevalent, where individuals seek medical treatment only after symptoms appear. Meanwhile, awareness of routine blood pressure control and the importance of maintaining a healthy lifestyle is still relatively low. On the other hand, public health center personnel face a high workload and limited time to implement educational and innovative activities, including complementary therapies. Based on these conditions, strengthening the role of human resources at Medan Deli Public Health Center is essential through capacity building of healthcare workers and community health cadres in education and the application of complementary therapy based on papaya juice for patients with hypertension. This approach aims to support blood pressure control and improve community health status in a sustainable manner, while empowering health personnel to become agents of change within the community. Consequently, hypertension management can be carried out sustainably at the household level. The use of papaya juice as a complementary therapy may serve as a natural alternative to support hypertension control, particularly for communities with limited access to medications or healthcare facilities. The Community Service Program titled “Strengthening the Role of Human Resources in Hypertension Management through Papaya Juice-Based Complementary Therapy” successfully increased community knowledge and skills in managing hypertension naturally and independently. Papaya juice has been scientifically proven to help reduce blood pressure, and the active involvement of human resources played a key role in the success of community-based hypertension control efforts.